Characterization and genomic analysis of a Herelleviridae bacteriophage UHP46 infecting mastitis-causing Staphylococcus aureus - Najeeb, Sara; Khan, Imran; Muhammad, Javed; Jahangir, Muhammad; Alvi, Iqbal Ahmad; Abbas, Anza; Ullah, Aman; Ullah, Arif; Sajjad, Wajiha; Khan, Hashir; Khan, Amjad (Frontiers in Microbiology, 2025)
BackgroundMastitis is a widespread disease on a global scale, significantly impacting the dairy industry. Mastitis in dairy cattle is caused by over 150 different bacteria, with Staphylococcus aureus (S. aureus) playing a significant role in financial losses, problems with animal welfare, and challenges with food safety. Phage treatment is thus being investigated as an effective replacement for reducing contaminants and illnesses caused by bacteria. In this study, we identified a phage UHP46, that effectively targets mastitis-causing S. aureus.MethodsS. aureus S46 was used to screen for the wastewater lytic phages. The isolated lytic phage UHP46, which formed clear plaques and spots, was further characterized.ResultsPhage UHP46, belonging to the Herelleviridae family, forms clear, circular plaques in bacterial lawn. UHP46 showed stability under various range of temperature and pH levels, with maximum activity observed at pH 7 and temperature 37°C. Genomic analysis revealed that phage UHP46 is a dsDNA virus with an approximate genome size of 139,731 bp, and it encodes 72 proteins with known functions and 136 hypothetical proteins. One-step growth curve analysis indicated latent period of approximately 20 mins and burst size of about 27 progeny/cell. In organic stability test, UHP46 showed stability in DMSO and acetone. Furthermore, it effectively inhibited S. aureus growth for up to 16 h, suggesting its suitability for therapeutic applications against S. aureus infections.ConclusionThese findings suggest that phage UHP46 could serve as a promising alternative to antibiotics for managing S. aureus- induced mastitis, contributing to dairy production and improved animal health.